In vitro regeneration of semecarpus anacardium L. from axenic seedling-derived nodal explants - Panda, Bhuban Mohan; Hazra, Sulekha (Trees-Structure and Function, 2010)
Semecarpus anacardium (Anacardiaceae), a deciduous forest tree, is a potent source of medicinal compounds. Poor seed viability of this species limits the conventional propagation practice. Proliferation of shoots from axillary meristem was achieved in semisolid WPM medium supplemented with BAP 4.44 mu M and KN 4.64 mu M. Factors including culture vessels, gelling agents and antioxidants were identified and optimized for proliferation and growth of shoots in vitro. Cotton-plugged culture vessels were more favorable. Phytagel 0.2% as gelling agent and activated charcoal 0.2% as antioxidant were superior to other agents and antioxidants tested. All the shoots rooted in half-strength WPM liquid medium with IBA 2.46 mu M. Rooted shoots survived (91%) in the soil-sand 1:1 mixture. Ex vitro rooting of shoots and hardening of plants were achieved in 80% of the explants in the soil-sand mixture. Hardened plants were maintained in a greenhouse. This is the first report on in vitro regeneration of Semecarpus anacardium.
Keywords: Antioxidants; Culture vessels; Ex vitro rooting; Gelling agents; Medicinal tree; micropropagation

Micropropagation of semecarpus anacardium L.: a medicinally important tree species - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biosystems, 2012)
Semecarpus anacardium L., a deciduous forest tree, is a source of medicinal compounds. Poor seed-viability restricts the conventional propagation. Micropropagation protocol is standardized for this species. Shoot culture-derived nodal explants were cultured in woody plant media supplemented with thidiazuron (TDZ). Shoot differentiation from meristem was limited. Meristems swelled to form meristematic mass in higher concentrations of TDZ. Swelling of meristem was attributed to the proliferation of meristematic cells. Development of shoots from meristematic mass on withdrawal of TDZ in culture medium indicated the inhibitory influence of TDZ on differentiation of buds to form shoots. Harvesting the primary shoot, leads to appearance of additional shoot buds which elongated on repeated transfer of explants in a medium devoid of growth regulator every four weeks. Optimum (17) number of shoots obtained from each meristem in explants pre-cultured in TDZ 2.27 mu M and re-cultured in growth regulator free medium for seven cycles (28 weeks). This confirms the stimulatory influence of TDZ on proliferation of meristem and inhibitory influence on shoot differentiation. All shoots, rooted in the medium with Indole butyric acid 2.46 mu M. Plantlets survived on transfer to sand: soil (1: 1) mixture and acclimatized. This is the first report on micropropagation of S. anacardium from seedling derived nodal buds using TDZ.
Keywords: Meristematic; micropropagation; Semecarpus anacardium L.; thidiazuron